Chemical composition of four forage grasses from the state of Jalisco - Sosa-Montes, Eliseo; Sánchez-Sánchez, Zaira Sarahi; Mendoza-Pedroza, Sergio Iban; Ramírez-Bribiesca, Efrén; González-Cerón, González-Cerón; Vaquera Huerta, Humberto (Revista Mexicana de Ciencias Agrícolas, 2022)
In the Mexican tropics, livestock farming is based on extensive production systems, and it is important to know the nutritional content of forages, therefore the objective of this study was to evaluate the chemical composition of: Cenchrus ciliaris L., Megathyrsus maximus cv Guinea, Ixophorus unisetus and Megathyrsus maximus cv Tanzania, grasses established and frequently used in the Tropics for animal feed. The samples from the locality ‘San Luis Tenango’, Tonaya, Jalisco were analyzed at the Laboratory of Animal Nutrition, Department of Zootechnics, Chapingo Autonomous University. The following was determined: ashes (Ash), crude protein (CP), ethereal extract (EE), neutral detergent fiber (NDF), cellular content (CC), acid detergent fiber (ADF) and cellulose (Cel). Data analysis was performed with three repetitions and each repetition was considered an experimental unit. Pearson’s correlation and the separation of means by Tukey (p< 0.05) were performed. CP was positively correlated with Ash and CC and negatively correlated with NDF and ADF (p< 0.05). Megathyrsus maximus cv Guinea was the forage species with the highest amount of CP (12.9 g (100 g)-1), followed by (p< 0.05) Megathyrsus maximus cv Tanzania (8.7 g (100 g)-1). Megathyrsus maximus cv Guinea showed the highest percentage of Ash, 11.7 g (100 g)-1 and the lowest values of ADF and Cel and its NDF value (74.8 g (100 g)-1) was low (p< 0.05), slightly higher than that of Ixophorus unisetus (73.5 g (100 g)-1). Therefore, Megathyrsus maximus cv Guinea was the grass with the highest nutritional value.